2012
DOI: 10.1021/jp303980x
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Monolayers in Mesoporous Silicon

Abstract: Herein, redox reactions at chemically derivatized porous silicon (PSi) films are investigated. Passivation of the PSi matrix, by replacing metastable Si−H termini with nonpolar SiCCR linkages, allows the electrochemical PSi device to operate in aqueous environments under oxidizing conditions (i.e., electron hole accumulation regime). Cu(I)-catalyzed alkyne−azide cycloaddition reactions are used to anchor ferrocene derivatives and probe electrochemical reactions at the exceedingly large surface area-to-volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 119 publications
0
13
0
Order By: Relevance
“…4). For the H-PSi wafers before the reaction, the peak for Si-H vibrations around 2100 cm −1 was obvious, 15,16 but completely and partly disappeared after the experiment for 2.5 h in the absence and presence of light, respectively. These results indicated that both reactions should display different degradation mechanisms.…”
Section: Resultsmentioning
confidence: 97%
“…4). For the H-PSi wafers before the reaction, the peak for Si-H vibrations around 2100 cm −1 was obvious, 15,16 but completely and partly disappeared after the experiment for 2.5 h in the absence and presence of light, respectively. These results indicated that both reactions should display different degradation mechanisms.…”
Section: Resultsmentioning
confidence: 97%
“…We have recently reported the modification of PSi with this same surface chemistry to allow the PSi to be used as a high surface area and low capacitance electrode. 6 As we characterized the surface chemistry using XPS, FTIR spectroscopy and electrochemistry in that previous report, here we will concentrate our discussion on the reflectivity measurements shown in Fig. 2.…”
Section: Demonstration Of Using Psi Multimodal Detectors To Monitor Cmentioning
confidence: 99%
“…1), 23 and pore diameters were in the range of 5-20 nm. 6 The high-reflection wavelength can vary over a wide range and depends on both the thickness and refraction index contrast of the alternating H and L layers. As is shown in Fig.…”
Section: Preparation and Characterization Of Psi Optical Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…This shadows the semiconducting properties of Si and becomes more critical for nanoscale devices whose output will be dominated by the SiO x layer . Conventionally, self-assembled monolayers comprising alkyl chains are used to protect Si from oxidation by blocking oxygen and water from reaching the bulk silicon. , This however comes with an expense of the need for complicated fabrication procedures that often require external effects, such as heat, light, or radical initiators, to enable the formation of covalent bonds between the monolayer-forming molecules and the surface. In addition, the length of the alkyl chain on the molecules in the monolayer should be long enough to enable efficient packing . However, longer-chain molecules also come with the expense of blocking electron transfer. Packing defects in monolayers, which allows for oxygen and water to reach the Si surface, lead to monolayer degradation over time. ,, Hence, there is a need to find a procedure to protect Si from oxidation while preserving the electron-transferring capability of the protecting layer.…”
Section: Introductionmentioning
confidence: 99%